3D printing of optical components - Siva Selvaraju (Nanyang Technological University, 2022)
The norm of printing consists of a printer that prints text or images on a piece of paper. Through technological advancements, we can create 3-Dimensional (3D) objects using a printer. Using a 3D printer, a range of objects can be fabricated, ranging from screws up to a boat of a size of 7.72m. Now if you ever lose a bolt or want to personalise a gift, you could always print it out. This report will be exploring 3D printing of optical components. Digital light processing (DLP) 3D printing technique will be used to experiment with the findings with its higher level of precision. DLP 3D printing uses ultraviolet (UV) to cure liquid resin into hardened plastic. This report will dive into researching, developing, and testing on a 3D printer to experiment on optical components.